AB1388 Quality of life and health care use in an early arthritis cohort: Comparison between patients with early RA and patients with inflammatory arthralgias. (23rd January 2014) - Kuijper, T.; Luime, J.; Bindels, P.; Hazes, J.
Abstract : Background: Current evidence shows that early treatment of arthritis results in a more favorable course of disease. As patients are referred to the rheumatologist at an earlier stage of disease, patients presenting with inflammatory arthralgias, for whom no evident synovitis can be detected at physical examination, are increasingly seen by rheumatologists. A previous study suggested that the burden of disease for this patient group equals the burden of disease in early RA patients [1]. As formal diagnoses and decent insights in the pathophysiological processes underlying the complaints are usually lacking, little is known about the progression of health complaints over time, as well as its consequences on functional ability, health, general well-being and health care use (HCU). Objectives: To compare the burden of disease (pain, health related quality of life, functional ability, fatigue) and health care consumption levels of patients referred to the early arthritis clinic being diagnosed as having inflammatory arthralgias without clinical synovitis to patients with clinical RA. Methods: Patients with clinical RA and patients with inflammatory arthrialgias participating in the Rotterdam Early Arthritis Cohort before the date of June 2009 were selected. Data were used measuring the domains pain (RADAI), health related quality of life (SF-36), functionally ability (HAQ), fatigue (FAQ and VAS) and health care use at baseline and at 6 and 12 months of follow-up. Poisson regression for repeated data was performed to identify demographic, clinical and psychosocial factors associated with high overall use of services. Results: 276 patients with inflammatory arthralgias without synovitis and 225 RA patients were included. Pain scores (RADAI) decreased in over time in both groups. A trend was seen for a higher pain scores at baseline and lower pain scores after 6 and 12 months in the RA group. In the RA group, functional ability (HAQ) scores were worse at baseline and decreased over time, while remaining more or less constant in the inflammatory arthralgias group. Fatigue scores (FAS) were similar in both groups and remained constant over time. Health related quality of life (SF-36 subscales) is comparable or somewhat lower for the RA group, improving over time for both groups. However, HRQOL remained considerably lower than the population average in both groups. Health care utilization decreased over time and was similar in both groups, except for higher medical specialist visits in the RA group. High levels of HCU were associated with increased pain (IRR 1.14, 95%>CI 1.07–1.21) and worse mental health (IRR 1.03, 95%>CI 1.01-1.04) in the inflammatory arthralgias group and with increased pain (IRR 1.06, 95%>CI 1.02-1.11), shorter duration of complaints (IRR 1.59, 95%>CI 1.21-2.09), increased fatigue (IRR 1.02, 95%>CI 1.00-1.03), living together (IRR 1.34, 95%>CI 1.01-1.77) and low chance locus of control (IRR 1.03, 95%>CI 1.01-1.05) in the RA group. Conclusions: Overall, the burden of disease in patients with inflammatory arthralgias is similar to that of patients with RA, improving over time in both groups. Fatigue did not improve in either group. HCU was slightly higher in the RA group, decreasing over time in both groups. References: Geuskens G et al 2008. Disclosure of Interest: None Declared